Decreased isometric neck strength is a risk factor for head, neck and face injuries in professional rugby league players - Hides, J. A.; Brown, D. A.; Anning, L. N.; Blanch, P. D.; Leung, F. T. (Journal of Sports Sciences, 2024)
Head, neck and face injuries are a concern in contact sports. This exploratory study aimed to establish 1) injury risk factors for head, neck and face injuries and 2) clinical cut-off values related to strength, endurance and proprioception of the cervical spine in a team of professional rugby league players. Pre-season assessments of isometric strength of the flexor, extensor and lateral flexor muscles, endurance of the flexor muscles and joint position error were conducted. Injuries resulting in games missed were recorded. Cross-tabulations were used to determine the unadjusted odds ratios for the measures as risk factors for playing season injuries. The unadjusted odds ratio (OR) values indicated that if a player had weaker extensors of the neck (<36.4 kg, p = 0.014; <3.4N/kg, p = 0.014) or asymmetry of isometric strength of their lateral flexor muscles (left-to-right ratio <0.91, p = 0.005), their odds of games missed due to season head, neck and face injuries was increased (OR extensors = 8; 95% CI = 1.5-42.5 OR asymmetry of lateral flexor muscles OR = 12.6; 95% CI = 2.0-79.4). As muscle strength is modifiable, the clinical application of this study would involve targeting players in the team beneath the clinical cut-off value.